Retained Placenta Accreta Mimicking Choriocarcinoma - Maureen P. Kohi; Gabrielle A. Rizzuto; Nicholas Fidelman; Jennifer Lucero; Mari-Paule Thiet (Case Reports in Pathology)
This case demonstrates a rare event of retained invasive placenta masquerading as choriocarcinoma. The patient presented with heavy vaginal bleeding following vaginal delivery complicated by retained products of conception. Ultrasound and computed tomography demonstrated a vascular endometrial mass, invading the uterine wall and raising suspicion for choriocarcinoma. Hysterectomy revealed retained invasive placenta.